Heating binder for high-strength cold-pressed ball, high-strength cold-pressed ball and preparation method of high-strength cold-pressed ball
By using a heat binder for high-strength cold pressed balls in cold pressed balls, combining physical bonding and chemical consolidation, an organic-inorganic doping network structure is formed, and the cold pressed balls have low strength and high powdering rate. The problem is that efficient consolidation and compressive resistance are achieved, reducing costs and pollution.
Patent Information
- Application Number
- CN202411288187.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-14
- Publication Date
- 2024-12-13
AI Technical Summary
The existing cold pressed pellets have low strength and high pulverization rate, which leads to a large amount of investment in binder to increase costs, which is not conducive to environmental protection.
Use heat binder for high-strength cold pressing balls, including components A and components B. Component A contains calcium silicate, sodium silicate, potassium aluminum sulfate, sodium fluorosilicate and anhydrous magnesium chloride. Component B It contains starch, carboxymethyl cellulose and pretreated sodium bentonite, which is prepared by sonication and drying, forming an organic-inorganic doping network structure, combining physical bonding and chemical consolidation to enhance the consolidation force of the pellets and Compressive strength.
It significantly improves the compressive strength and drop strength of cold pressed pellets, reduces the powdering rate, improves the utilization rate of sludge dust removal ash, saves energy, reduces pollution, and significantly improves the metallurgical effect in steelmaking production.
Smart Images

Figure CN119120895A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of exothermic adhesives, and in particular to an exothermic adhesive for high-strength cold-pressed balls, high-strength cold-pressed balls and a preparation method thereof. Background Art
[0002] Cold pressed balls refer to the process of mixing iron ore concentrate and a binder and then compressing them under a certain external pressure to form a block material with a certain strength. After a series of treatments, it is hardened and consolidated, and then put into a furnace for smelting. This can fully utilize resources and reduce production costs and environmental pollution.
[0004] Compared with common adhesives, cold pressed pellet binders have better bonding effects, but pellet binders are only a carrier, and the time from powder bonding to furnace smelting is short. Although there are many binders available, they are easy to cause low strength of pressed pellets and high powdering rate. In order to ensure the bonding effect, a large amount of investment is required, which not only increases costs, but is also not conducive to environmental protection. Summary of the invention
[0005] The purpose of the present invention is to solve the shortcomings of the prior art and to propose a heating adhesive for high-strength cold-pressed balls, high-strength cold-pressed balls and a preparation method thereof.
[0006] A high-strength exothermic binder for cold-pressed balls comprises: a component A and a component B, wherein the mass ratio of the component A to the component B is 1-5:5-10; the raw materials of the component A comprise, by mass, 10-20 parts of calcium silicate, 5-10 parts of sodium silicate, 1-5 parts of potassium aluminum sulfate, 1-5 parts of sodium fluorosilicate, 1-3 parts of anhydrous magnesium chloride, 0.1-1 parts of a cross-linking agent, and 0.01-0.1 parts of an initiator; the raw materials of the component B comprise, by mass, 20-30 parts of starch, 1-2 parts of carboxymethyl cellulose, and 10-20 parts of pretreated sodium bentonite.
[0007] Preferably, the cross-linking agent is at least one of hexamethylenetetramine, hydroquinone, polyethyleneimine and p-phenylenediamine.
[0008] Preferably, the initiator is a persulfate.
[0009] More preferably, the initiator is at least one of ammonium persulfate, potassium persulfate and sodium persulfate.
[0010] Preferably, the pretreated sodium bentonite is prepared by the following specific operation: adding sodium bentonite to a methylamine solution and ultrasonically treating it for 10-30 minutes, adding acrylamide thereto and continuing ultrasonically treating it for 1-2 hours, filtering, washing, and vacuum drying.
[0011] More preferably, the mesh number of the sodium bentonite is 300-350 mesh, wherein the montmorillonite content is 65-80%, and the Na2O content is 1.5-1.8%.
[0012] More preferably, the mass fraction of the methylamine solution is 1-5%, and the mass ratio of sodium bentonite, methylamine solution and acrylamide is 10-20:30-60:1-5.
[0013] More preferably, the ultrasound frequency is 5-15 kHz.
[0014] A high-strength cold-pressed ball comprises: the above-mentioned exothermic binder for high-strength cold-pressed balls and sludge dust removal ash; the mass ratio of the sludge dust removal ash to the component A in the above-mentioned exothermic binder for high-strength cold-pressed balls is 100-200:1-5.
[0015] The preparation method of the above-mentioned high-strength cold-pressed balls comprises the following steps: adding component A of the above-mentioned exothermic binder for high-strength cold-pressed balls to sludge dust removal ash, adding water thereto until the water content of the system is 2.2-4%, stirring evenly, adding component B of the above-mentioned exothermic binder for high-strength cold-pressed balls thereto under stirring, continuing stirring for 1-3 minutes, making balls, consolidating in the air for 10-20 hours, and then drying at 150-200°C for 30-50 minutes. Beneficial Effects
[0016] The cold pressed balls of the present invention are initially consolidated mainly by physical bonding of component B. As the consolidation time increases, chemical consolidation phases are continuously generated. On the one hand, the consolidation force of the balls is increased to avoid pulverization. On the other hand, in conjunction with the action of component A, the strength at the later stage of solidification can be significantly enhanced. The cold pressed balls have excellent compressive strength and drop strength, and a low pulverization rate.
[0017] The sodium bentonite used in the present invention is easier to be intercalated and combined with acrylamide monomer after stripping, which can not only effectively inhibit the problem of easy agglomeration of the sodium bentonite, but also has excellent dispersibility with starch and carboxymethyl cellulose. On the one hand, the addition amount is low, and on the other hand, the bonding and molding effect is good, and the pulverization rate is effectively reduced; and the anhydrous magnesium chloride in the A component will quickly release a large amount of heat when it meets water, which can ensure that the temperature of the cold-pressed pellets reaches above 90°C, and the sodium bentonite pretreated in a high-temperature environment and the hydration process of the A component are in-situ polymerized to form an organic-inorganic doped network structure, which not only effectively improves the strength and stability of the pellets, but also has high compressive strength and drop strength, and the formed tightly combined structure can also promote the temperature to continue to rise, thereby ensuring the drying speed and drying efficiency of the pellets.
[0018] The exothermic binder for cold-pressed balls obtained by the present invention can effectively improve the strength of cold-pressed balls made from sludge dust ash and reduce its pulverization rate, which can not only fully improve the utilization rate of sludge dust ash, but also save energy and reduce pollution. When used in steelmaking production, it has a significant metallurgical effect, reduces the consumption of steel materials, and promotes the comprehensive utilization of resources. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 It is a comparison chart of the drop strength and compressive strength of the cold-pressed balls obtained in Example 5 and Comparative Examples 1-2.
[0020] Figure 2 The figure is a comparison chart of the pulverization rate and bursting temperature of the cold-pressed balls obtained in Example 5 and Comparative Examples 1-2. DETAILED DESCRIPTION
[0021] The present invention will be further explained below in conjunction with specific embodiments.
[0022] The sodium bentonite used below was purchased from Lingshou County Derui Mining Co., Ltd., and its parameters are as follows: 350 mesh, montmorillonite content of 73.47%, and Na2O content of 1.69%.
[0023] The sludge dust removal ash used below is from Tangshan Iron and Steel Group, and its parameters are as follows: TFe 50.27%, FeO 9.33%, SiO24.73%, CaO 4.93%, MgO 1.05%, A12030.45%, S 0.071%, P 0.025%, and C 10.2%. Example 1
[0024] A heat-generating adhesive for high-strength cold-pressed balls comprises: a component A and a component B, wherein the mass ratio of the component A to the component B is 1:5.
[0025] The raw materials of component A include: 10 kg calcium silicate, 5 kg sodium silicate, 1 kg potassium aluminum sulfate, 1 kg sodium fluorosilicate, 1 kg anhydrous magnesium chloride, 0.1 kg hexamethylenetetramine, and 0.01 kg potassium persulfate.
[0026] The raw materials of component B include: 20 kg starch, 1 kg carboxymethyl cellulose, and 10 kg pretreated sodium bentonite; wherein the pretreated sodium bentonite is prepared by the following specific operation: 10 kg sodium bentonite is added to 30 kg 1% methylamine solution by mass, ultrasonically treated for 10 minutes at an ultrasonic frequency of 5 kHz, 1 kg acrylamide is added thereto, and ultrasonic treatment is continued for 1 hour, filtered, washed, and vacuum dried.
[0027] A high-strength cold-pressed ball comprises: the above-mentioned exothermic binder for high-strength cold-pressed balls and sludge dust removal ash; the mass ratio of the sludge dust removal ash to the component A in the above-mentioned exothermic binder for high-strength cold-pressed balls is 100:1.
[0028] The preparation method of the above-mentioned high-strength cold-pressed balls comprises the following steps: adding component A of the above-mentioned exothermic binder for high-strength cold-pressed balls to sludge dust removal ash, adding water thereto until the water content of the system is 2.2%, stirring evenly, adding component B of the above-mentioned exothermic binder for high-strength cold-pressed balls thereto under stirring, continuing stirring for 1 minute, making balls, consolidating in the air for 10 hours, and then drying at 150°C for 30 minutes. Example 2
[0029] A high-strength exothermic adhesive for cold-pressed balls comprises: a component A and a component B, wherein the mass ratio of the component A to the component B is 1:2.
[0030] The raw materials of component A include: 20 kg calcium silicate, 10 kg sodium silicate, 5 kg potassium aluminum sulfate, 5 kg sodium fluorosilicate, 3 kg anhydrous magnesium chloride, 1 kg hydroquinone, and 0.1 kg ammonium persulfate.
[0031] The raw materials of component B include: 30 kg of starch, 2 kg of carboxymethyl cellulose, and 20 kg of pretreated sodium bentonite; wherein the pretreated sodium bentonite is prepared by the following specific operation: 20 kg of sodium bentonite is added to 60 kg of 5% methylamine solution by mass, ultrasonically treated for 30 minutes at an ultrasonic frequency of 15 kHz, 5 kg of acrylamide is added thereto, and ultrasonic treatment is continued for 2 hours, filtered, washed, and vacuum dried.
[0032] A high-strength cold-pressed ball comprises: the above-mentioned exothermic binder for high-strength cold-pressed balls and sludge dust removal ash; the mass ratio of the sludge dust removal ash to the component A in the above-mentioned exothermic binder for high-strength cold-pressed balls is 40:1.
[0033] The preparation method of the above-mentioned high-strength cold-pressed balls comprises the following steps: adding component A of the above-mentioned exothermic binder for high-strength cold-pressed balls to sludge dust removal ash, adding water thereto until the water content of the system is 4%, stirring evenly, adding component B of the above-mentioned exothermic binder for high-strength cold-pressed balls thereto under stirring, continuing stirring for 3 minutes, making balls, consolidating in air for 20 hours, and then drying at 200°C for 50 minutes. Example 3
[0034] A heat-generating adhesive for high-strength cold-pressed balls comprises: a component A and a component B, wherein the mass ratio of the component A to the component B is 1:4.
[0035] The raw materials of component A include: 12 kg calcium silicate, 8 kg sodium silicate, 2 kg potassium aluminum sulfate, 4 kg sodium fluorosilicate, 1.5 kg anhydrous magnesium chloride, 0.7 kg polyethyleneimine, and 0.03 kg potassium persulfate.
[0036] The raw materials of component B include: 28 kg of starch, 1.3 kg of carboxymethyl cellulose, and 18 kg of pretreated sodium bentonite; wherein the pretreated sodium bentonite is prepared by the following specific operation: 13 kg of sodium bentonite is added to 50 kg of 2% methylamine solution by mass, ultrasonically treated for 25 min at an ultrasonic frequency of 8 kHz, 4 kg of acrylamide is added thereto, and ultrasonic treatment is continued for 80 min, filtered, washed, and vacuum dried.
[0037] A high-strength cold-pressed ball comprises: the above-mentioned exothermic binder for high-strength cold-pressed balls and sludge dust removal ash; the mass ratio of the sludge dust removal ash to the component A in the above-mentioned exothermic binder for high-strength cold-pressed balls is 90:1.
[0038] The preparation method of the above-mentioned high-strength cold-pressed balls comprises the following steps: adding component A of the above-mentioned exothermic binder for high-strength cold-pressed balls to sludge dust removal ash, adding water thereto until the water content of the system is 3.5%, stirring evenly, adding component B of the above-mentioned exothermic binder for high-strength cold-pressed balls thereto under stirring, continuing stirring for 1.5 minutes, making balls, consolidating in air for 18 hours, and then drying at 160°C for 45 minutes. Example 4
[0039] A high-strength exothermic adhesive for cold-pressed balls comprises: a component A and a component B, wherein the mass ratio of the component A to the component B is 2:3.
[0040] The raw materials of component A include: 18 kg calcium silicate, 6 kg sodium silicate, 4 kg potassium aluminum sulfate, 2 kg sodium fluorosilicate, 2.5 kg anhydrous magnesium chloride, 0.3 kg p-phenylenediamine, and 0.07 kg sodium persulfate.
[0041] The raw materials of component B include: 22 kg of starch, 1.7 kg of carboxymethyl cellulose, and 12 kg of pretreated sodium bentonite; wherein the pretreated sodium bentonite is prepared by the following specific operation: 17 kg of sodium bentonite is added to 40 kg of 4% methylamine solution by mass, ultrasonically treated for 15 minutes at an ultrasonic frequency of 12 kHz, 2 kg of acrylamide is added thereto and ultrasonically treated for 100 minutes, filtered, washed, and vacuum dried.
[0042] A high-strength cold-pressed ball comprises: the above-mentioned exothermic binder for high-strength cold-pressed balls and sludge dust removal ash; the mass ratio of the sludge dust removal ash to the component A in the above-mentioned exothermic binder for high-strength cold-pressed balls is 30:1.
[0043] The preparation method of the above-mentioned high-strength cold-pressed balls comprises the following steps: adding component A of the above-mentioned exothermic binder for high-strength cold-pressed balls to sludge dust removal ash, adding water thereto until the water content of the system is 2.5%, stirring evenly, adding component B of the above-mentioned exothermic binder for high-strength cold-pressed balls thereto under stirring, continuing stirring for 2.5 minutes, making balls, consolidating in the air for 12 hours, and then drying at 180°C for 35 minutes. Example 5
[0044] A heat-generating adhesive for high-strength cold-pressed balls comprises: a component A and a component B, wherein the mass ratio of the component A to the component B is 3:7.
[0045] The raw materials of component A include: 15 kg calcium silicate, 7 kg sodium silicate, 3 kg potassium aluminum sulfate, 3 kg sodium fluorosilicate, 2 kg anhydrous magnesium chloride, 0.5 kg polyethyleneimine, and 0.05 kg ammonium persulfate.
[0046] The raw materials of component B include: 25 kg of starch, 1.5 kg of carboxymethyl cellulose, and 15 kg of pretreated sodium bentonite; wherein the pretreated sodium bentonite is prepared by the following specific operation: 15 kg of sodium bentonite is added to 45 kg of 3% methylamine solution by mass, ultrasonically treated for 20 minutes at an ultrasonic frequency of 9 kHz, 3 kg of acrylamide is added thereto, and ultrasonic treatment is continued for 90 minutes, filtered, washed, and vacuum dried.
[0047] A high-strength cold-pressed ball comprises: the above-mentioned exothermic binder for high-strength cold-pressed balls and sludge dust removal ash; the mass ratio of the sludge dust removal ash to the component A in the above-mentioned exothermic binder for high-strength cold-pressed balls is 50:1.
[0048] The preparation method of the above-mentioned high-strength cold-pressed balls comprises the following steps: adding component A of the above-mentioned exothermic binder for high-strength cold-pressed balls to sludge dust removal ash, adding water thereto until the water content of the system is 3%, stirring evenly, adding component B of the above-mentioned exothermic binder for high-strength cold-pressed balls thereto under stirring, continuing stirring for 2 minutes, making balls, consolidating in the air for 15 hours, and then drying at 170°C for 40 minutes.
[0049] Comparative Example 1 A heat-generating adhesive for high-strength cold-pressed balls comprises: a component A and a component B, wherein the mass ratio of the component A to the component B is 3:7.
[0050] The raw materials of component A include: 15 kg calcium silicate, 7 kg sodium silicate, 3 kg potassium aluminum sulfate, 3 kg sodium fluorosilicate, 0.5 kg polyethyleneimine, and 0.05 kg ammonium persulfate.
[0051] The raw materials of component B include: 25 kg of starch, 1.5 kg of carboxymethyl cellulose, and 15 kg of pretreated sodium bentonite; wherein the pretreated sodium bentonite is prepared by the following specific operation: 15 kg of sodium bentonite is added to 45 kg of 3% methylamine solution by mass, ultrasonically treated for 20 minutes at an ultrasonic frequency of 9 kHz, 3 kg of acrylamide is added thereto, and ultrasonic treatment is continued for 90 minutes, filtered, washed, and vacuum dried.
[0052] A high-strength cold-pressed ball comprises: the above-mentioned exothermic binder for high-strength cold-pressed balls and sludge dust removal ash; the mass ratio of the sludge dust removal ash to the component A in the above-mentioned exothermic binder for high-strength cold-pressed balls is 50:1.
[0053] The preparation method of the above-mentioned high-strength cold-pressed balls comprises the following steps: adding component A of the above-mentioned exothermic binder for high-strength cold-pressed balls to sludge dust removal ash, adding water thereto until the water content of the system is 3%, stirring evenly, adding component B of the above-mentioned exothermic binder for high-strength cold-pressed balls thereto under stirring, continuing stirring for 2 minutes, making balls, consolidating in the air for 15 hours, and then drying at 170°C for 40 minutes.
[0054] Comparative Example 2 A heat-generating adhesive for high-strength cold-pressed balls comprises: a component A and a component B, wherein the mass ratio of the component A to the component B is 3:7.
[0055] The raw materials of component A include: 15 kg calcium silicate, 7 kg sodium silicate, 3 kg potassium aluminum sulfate, 3 kg sodium fluorosilicate, 2 kg anhydrous magnesium chloride, 0.5 kg polyethyleneimine, and 0.05 kg ammonium persulfate.
[0056] The raw materials of component B include: 25 kg starch, 1.5 kg carboxymethyl cellulose, and 15 kg sodium bentonite.
[0057] A high-strength cold-pressed ball comprises: the above-mentioned exothermic binder for high-strength cold-pressed balls and sludge dust removal ash; the mass ratio of the sludge dust removal ash to the component A in the above-mentioned exothermic binder for high-strength cold-pressed balls is 50:1.
[0058] The preparation method of the above-mentioned high-strength cold-pressed balls comprises the following steps: adding component A of the above-mentioned exothermic binder for high-strength cold-pressed balls to sludge dust removal ash, adding water thereto until the water content of the system is 3%, stirring evenly, adding component B of the above-mentioned exothermic binder for high-strength cold-pressed balls thereto under stirring, continuing stirring for 2 minutes, making balls, consolidating in the air for 15 hours, and then drying at 170°C for 40 minutes.
[0059] The drop strength of the cold-pressed balls obtained in Example 5 and Comparative Examples 1-2 was measured as follows: the same number of cold-pressed balls were randomly selected from each group, and a single cold-pressed ball was freely dropped from a height of 0.5 m onto a 10 cm thick steel plate. If it broke after falling n times, the drop strength of the cold-pressed ball was (n-1) times / 0.5 m, and the average value was taken as the drop strength of the cold-pressed balls in this group.
[0060] The compressive strength of the cold-pressed balls obtained in Example 5 and Comparative Examples 1-2 was measured as follows: each group of cold-pressed balls was placed in a universal testing machine for individual testing, and the pressure value when the balls broke was recorded, which was the compressive strength of the group of cold-pressed balls.
[0061] like Figure 1 As shown, the drop strength and compressive strength of the cold-pressed balls obtained in Example 5 are the highest, which are better than those in Comparative Examples 1-2 (P < 0.05).
[0062] The pulverization rate of the cold-pressed balls obtained in Example 5 and Comparative Examples 1-2 was measured as follows: the same mass ( W 0), slightly shake the container of cold pressed balls, pick out the cold pressed balls that still maintain their complete shape and weigh them ( W 1).
[0063] Powdering rate = (1- W 1 / W 0)×100% The bursting temperature of the cold pressed balls obtained in Example 5 and Comparative Examples 1-2 was measured with reference to the dynamic measurement method of AC Company of the United States, as follows: 50 cold pressed balls were randomly selected from each group and loaded into a drying cup, and the drying cup was placed in a vertical tube with a wind speed of 1.5 m / s (cold state). The cold pressed balls were taken out after staying in the furnace for 5 minutes, and the maximum temperature that the cold pressed balls could withstand when 4% (i.e., 2 cold pressed balls were broken) was taken as the bursting temperature.
[0064] like Figure 2 As shown, the cold-pressed balls obtained in Example 5 have the lowest pulverization rate and the highest bursting temperature, which are better than those in Comparative Examples 1-2 (P < 0.05).
[0065] The applicant believes that: this is because the cold-pressed balls of the present invention are mainly physically bonded by the B component at the beginning of consolidation. As the consolidation time is extended, the chemical consolidation phase is continuously generated. On the one hand, the consolidation force of the balls is increased to avoid pulverization. On the other hand, the late curing strength can be significantly enhanced by cooperating with the A component. The cold-pressed balls have excellent compressive strength and drop strength, and the pulverization rate is small. The present invention uses sodium bentonite, which is easier to be intercalated with acrylamide monomer after peeling, which can not only effectively inhibit the problem of easy agglomeration of sodium bentonite, but also has excellent dispersibility with starch and carboxymethyl cellulose. On the one hand, the addition amount is low, and on the other hand, the bonding and molding effect is good, which effectively reduces the pulverization rate; at the same time, the anhydrous magnesium chloride in the A component will quickly release a large amount of heat when it meets water, which can ensure that the temperature of the cold-pressed balls itself reaches above 90°C. The pre-treatment of sodium bentonite and the hydration process of the A component in a high temperature environment are in situ polymerized to form an organic-inorganic doped network structure, which not only effectively improves the strength and stability of the balls, but also has high compressive strength and drop strength, and the formed tightly bonded structure can promote the temperature to continue to rise, ensuring the drying speed and drying efficiency of the balls.
[0066] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A heat-generating adhesive for high-strength cold-pressed balls, characterized in that: include: Component A and component B, the mass ratio of component A to component B is 1-5:5-10; The raw materials of component A include, by mass: 10-20 parts of calcium silicate, 5-10 parts of sodium silicate, 1-5 parts of potassium aluminum sulfate, 1-5 parts of sodium fluorosilicate, 1-3 parts of anhydrous magnesium chloride, 0.1-1 parts of a crosslinking agent, and 0.01-0.1 parts of an initiator; The raw materials of component B include, by mass: 20-30 parts of starch, 1-2 parts of carboxymethyl cellulose, and 10-20 parts of pretreated sodium bentonite.
2. The high-strength exothermic adhesive for cold-pressed balls according to claim 1, characterized in that: The cross-linking agent is at least one of hexamethylenetetramine, hydroquinone, polyethyleneimine and p-phenylenediamine.
3. The heat-generating adhesive for high-strength cold-pressed balls according to claim 1, characterized in that: The initiator is persulfate.
4. The heat-generating adhesive for high-strength cold-pressed balls according to claim 3, characterized in that: The initiator is at least one of ammonium persulfate, potassium persulfate and sodium persulfate.
5. The heat-generating adhesive for high-strength cold-pressed balls according to claim 1, characterized in that: The pretreated sodium bentonite is prepared by the following specific operation: adding the sodium bentonite to a methylamine solution and ultrasonically treating it for 10-30 minutes, adding acrylamide thereto and continuing the ultrasonic treatment for 1-2 hours, filtering, washing, and vacuum drying.
6. The heat-generating adhesive for high-strength cold-pressed balls according to claim 5, characterized in that: The mesh number of sodium bentonite is 300-350 mesh, of which the montmorillonite content is 65-80% and the Na2O content is 1.5-1.8%.
7. The heat-generating adhesive for high-strength cold-pressed balls according to claim 5, characterized in that: The mass fraction of the methylamine solution is 1-5%, and the mass ratio of sodium bentonite, methylamine solution and acrylamide is 10-20:30-60:1-5.
8. The heat-generating adhesive for high-strength cold-pressed balls according to claim 5, characterized in that: The ultrasonic frequency is 5-15kHz.
9. A high-strength cold-pressed ball, characterized in that: include: The exothermic binder and sludge dust removal ash for high-strength cold-pressed balls as described in any one of claims 1 to 8; The mass ratio of the sludge dust removal ash to the component A in the exothermic binder for high-strength cold-pressed balls as described in any one of claims 1 to 8 is 100-200:1-5.
10. A method for preparing the high-strength cold-pressed ball according to claim 9, characterized in that: The method comprises the following steps: adding component A of the high-strength heat-generating binder for cold-pressed balls as described in any one of claims 1 to 8 to sludge dust removal ash, adding water thereto until the water content of the system is 2.2-4%, stirring evenly, adding component B of the high-strength heat-generating binder for cold-pressed balls as described in any one of claims 1 to 8 under stirring, continuing stirring for 1-3 minutes, making balls, consolidating in air for 10-20 hours, and then drying at 150-200° C. for 30-50 minutes.
